Determination of Calliphoridae (Insecta: Diptera) Succession on Pig Carcasses in Central Anatolia, Turkey - Cenk Önsoy; Ferhat Altunsoy (Journal of Advanced Research in Natural and Applied Sciences)
Insects function as a biological clock in determining the time elapsed after death which is also called minimum postmortem interval (PMImin). Particularly, Calliphoridae family members are the first colonizers. Alt-hough the succession behaviors of calliphorids are a potentially useful and accurate tool for determining the time of death, the accuracy of this method has been severely affected by geographical and regional differences in the succes-sion patterns. Therefore, the present study purposes to determine the seasonal activity and succession patterns of Calliphoridae on pig carcasses in Central Anatolia of Turkey and providing the reference data for accurate PMImin determination in forensic cases. The study was conducted in Eskişehir, Sulu Karaağaç Village located in Central Anatolia, Turkey. The study was carried out by collecting samples from twelve pig carcasses left on the field for each months of the year 2011-2012. During the study, Calliphora vicina, Calliphora vomitoria, Chrysomya albiceps, Lu-cilia illustris, Lucilia sericata, Pollenia labialis, and Pollenia rudis which belonging to the Calliphoridae family, were collected. Additionally, their activity on the pig carcasses was observed. Pollenia rudis is firstly recorded from Turkey with this study. This study provides to determine certain PMImin in Turkey and also reference data are pro-vided to solve crimes occurring in different seasons.